Anti-inflammatory Activity of the Gel Containing a Combination of Neem Leaf Extract and Shallot Extract - Sara Nurmala; Moerfiah Moerfiah; Restu T. Purnama (Pharmacology and Clinical Pharmacy Research)
Neem leaves (Azadirahcta indica A. Juss) and shallots (Allium cepa L) contain flavonoids that are effective as an antioxidant, antibacterial, and anti-inflammatory. The aim of this study was to determine the effective concentration and the duration of treatment of the anti-inflammatory activity of the gel containing a combination of neem leaf extract and shallot extract. These substances have a similar effect, and it is believed that these combinations may effective as an anti-inflammatory at small doses to reduce the side effects. The animals were randomly divided into 6 groups with 5 rats per group. The rats were wound-induced by incising its back (length 1.5 cm, depth 0.7 mm) and were observed for 8 days. Parameters measured were wound’s closure, color, and healing process. Statistical analysis showed that the most effective concentration as an anti-inflammatory was formula 1 (neem leaf extract 3.125%: shallots extract 4%) with the fastest healing time was 5 days. Thus, this formula is one of the effective treatment options for healing wounds.Keywords: neem leaves, shallots, anti-inflammatory, combination, gel